REINFORCED CONCRETE BEAM AND COLUMN PROGRAMMING BASED ON SNI:2847-2019 ON SMARTPHONE USING TEXAS INSTRUMENTS - Bagio, Toni Hartono; Baggio, Eugene Yudhistira; Mudjanarko, Sri Wiwoho; Naibaho, Pio Ranap Tua (ASTONJADRO, 2021)
The development of technology in the last few years can not be denied that it has developed very rapidly. In building construction, reinforced concrete beam and columns calculations also utilizing that technology development. Input data used to calculate reinforcement of beam and column are material property, section property and internal forces. Calculation of reinforcement beam using quadratic equation method and reinforcement column using Newton-Raphson method and divided-by-two method.Calculation results are flexural reinforcement As (longitudinal compression area) and As' (longitudinal tension area), shear reinforcement Av (transversal area) and S (distance of  Av), torsional reinforcement Avt (transversal area due to torsional and/or shear), S (distance of Avt), Along (longitudinal area due to torsional buckling), column circular reinforcement Atot (total of longitudinal area), column rectangular two faces reinforcement Atot (total of longitudinal area), column rectangular four faces reinforcement Atot (total of longitudinal area), column biaxial reinforcement Atot (total of longitudinal area).   The program determines As, As' and Atotal, the code is written using the Texas Instruments programming language, so that it can be applied to smartphones. Smartphone and manual calculation, for all cases not more than 5%, the calculation using Texas Instrument is accurate.